2015
DOI: 10.1109/tcsii.2014.2368617
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Implementation and Design of a New Single-Channel Electrooculography-Based Human–Machine Interface System

Abstract: This brief introduces a new and practical human-machine interface (HMI) system based on single-channel electrooculography (EOG) signals. The proposed system uses a consumer wireless recording device to collect EOG and employs new encoding/decoding paradigms to covey users' intentions with EOG from eye movements including blinking and looking up. The simplicity and mobility of the system provides a comfortable and practical solution to HMI. Furthermore, to reduce the hardware complexity and power consumption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…They classified three types of eye movements (upward, downward, and blinking) with an 84% classification accuracy. In the study by Wu et al they classified four classes of commands which were combined with three types of eye movements (double blink, single blink, and looking up) [ 15 ]. They measured single-channel EOG using a MindWave Mobile Headset (NeoroSky, San Jose, CA, USA), and the classification accuracy was 92.3%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They classified three types of eye movements (upward, downward, and blinking) with an 84% classification accuracy. In the study by Wu et al they classified four classes of commands which were combined with three types of eye movements (double blink, single blink, and looking up) [ 15 ]. They measured single-channel EOG using a MindWave Mobile Headset (NeoroSky, San Jose, CA, USA), and the classification accuracy was 92.3%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are several studies that developed goggle-type wearable EOG measurement systems to improve the user’s comfort by reducing preparation time [ 11 , 12 , 13 ]. However, the electrodes around the eyes often cause discomfort to the user, and this discomfort has been the motivation for many studies [ 14 , 15 , 16 , 17 ]. To simplify and improve user convenience, many studies have proposed new electrode placement that can replace conventional EOG electrode placement [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in our previous study, various kinds of EOG signals, such as looking towards different directions and blinking in different ways, can be used to indicate the user's intentions [8]. However, because the system proposed in this paper is primarily focused on practical aspects and is aimed at providing an alternative communication pathway for the disabled people, only both-eye double blinks (DB) will be used as control signals in this paper.…”
Section: B Eog Signalsmentioning
confidence: 99%
“…For example, eye gestures were analyzed again for the interface and control of appliances [ 25 ] and the solution to the drift problem [ 26 ] was also revised. Other research can be found where a novel encoding paradigm to convey users’ intentions is presented as a preliminary step to develop an HCI [ 27 ]. The only EOG-based GUIs oriented to physically disabled persons that can be found in the last three years are [ 28 ] and [ 29 ].…”
Section: Related Workmentioning
confidence: 99%